Filum terminale paraganglioma a diagnostic dilemmas- A case report - Pandey, Mithilesh Kumar; Barman, Debajit Ray; Dasgupta, Sibaji; Roy, Kaushik; Saha, Suniti Kumar (Asian Journal of Medical Sciences, 2015)
Filum terminale paraganglioma is a rare tumour with usual short segment spinal involvement (one or two segments) as described in various literatures. It can also present with long segment spinal involvement as in our case, the tumour has involved L4 to S1 segments. Prognosis of filum terminale paraganglioma is excellent after total excision as it is classified under WHO grade I tumor. Nonetheless, after subtotal removal, tumour recurrence can occur. Even such an extremely rare entity with a larger spectrum of presentation can be treated successfully by total removal of the tumour. Here we present a fi lum terminale paraganglioma which was diagnosed after histopathology and immuno-histochemistry. Patient made a full recovery after tumour removal. Asian Journal of Medical Sciences Vol.7(2) 2015 104-106